GEWAMED project and its linkage to food security mainstreaming in developing countries - Quagliariello R. (Mainstreaming gender dimensions in water management for food security and food safety, 2007)
This study mentions the following points : the multifunctionality of agriculture, the links of water resources management and gender mainstreaming, the feminisation of agriculture, the transfer of knowledge, the access to resources and the effect in food security and safety and the rural women empowerment and ICT development. The evolution of the gender condition is a very slow process and the basic importance of financial resources should not be ignored. Unfortunately, this problem is underestimated since gender equality is considered only the consequence of a social behaviour. This is not true. The governments commitment should include a strong, real economic effect, absolutely essential to turn theories into actions and to achieve greater equality and empowerment of women.
2. Regional Coordination Workshop of GEWAMED (Mainstreaming Gender Dimensions into Water Resources Development and Management in the Mediterranean Region), 2007/03/12-14, Larnaca (Cyprus)